The wonder boy of Whistle Stop [large type] : a novel - Flagg, Fannie (Random House Large Print, 2020)
Taking a final visit to the ghost town where his mother Ruth's Whistle Stop Café made its famous fried green tomatoes, Bud Threadgoode discovers new friends and surprises about the community's women while triggering unexpected changes in his daughter's life.